The Endocannabinoid System as a Window Into Microglial Biology and Its Relationship to Autism - Araujo, Daniel John; Tjoa, Karensa; Saijo, Kaoru (Frontiers in Cellular Neuroscience, 2019)
Microglia are the resident, innate immune cells of the central nervous system (CNS) and are critical in managing CNS injuries and infections. Microglia also maintain CNS homeostasis by influencing neuronal development, viability, and function. However, aberrant microglial activity and phenotypes are associated with CNS pathology, including autism spectrum disorder (ASD). Thus, improving our knowledge of microglial regulation could provide insights into the maintenance of CNS homeostasis as well as the prevention and treatment of ASD. Control of microglial activity is in part overseen by small, lipid-derived molecules known as endogenous cannabinoids (endocannabinoids). Endocannabinoids are one component of the endocannabinoid system (ECS), which also includes the enzymes that metabolize these ligands, in addition to cannabinoid receptor 1 (CB1) and 2 (CB2). Interestingly, increased ECS signaling leads to an anti-inflammatory, neuroprotective phenotype in microglia. Here, we review the literature and propose that ECS signaling represents a largely untapped area for understanding microglial biology and its relationship to ASD, with special attention paid to issues surrounding the use of recreational cannabis (marijuana). We also discuss major questions within the field and suggest directions for future research.